The Mediating Effect of Entrepreneurial Self-Efficacy between Business Incubator Funding and Business Success: A Conceptual Paper - Abualreesh, Mohammed; Ngah, Rohana; Abdul Kadir, Mohd Ali Bahari (Information Management and Business Review, 2023)
Business incubation plays a crucial role in sustaining business success in both emerging and developing countries. Business incubators help businesses in developing countries effectively use innovation to reduce poverty and sustain social and economic development and growth. This conceptual paper focuses on the effect of funding in business incubator practices on business success in the context of Palestine. Additionally, this study strives to establish the mediating effect of entrepreneurial self-efficacy on the relationship between funding and business success. This study will apply a quantitative approach to collect data from businesses in Palestine. The Partial Least Squares (PLS) method will be used to analyze the data. This study adopted a resource-based view (RBV), which claims that resources, skills, and capabilities are valuable tangible and intangible resources that lead to business success. If empirically supported, the proposed framework may provide effective assistance for business incubators, entrepreneurs, business owners, and managers in developing countries such as Palestine. Therefore, the results of this study will help provide academic research, future research, government, and related agencies with guiding principles and information.